A case study of blended e-learning in Thailand. Issue 2 (18th March 2020) - Wongwuttiwat, Jittima; Buraphadeja, Vasa; Tantontrakul, Tanakom
Abstract : Purpose: This case study aims to analyze and compare the learning achievements of two groups of university students taught by: traditional face-to-face learning (TDL) and blended e-learning (BEL). To the best of the authors' knowledge no previous study of the use of BEL in the context of Thailand has addressed the same purpose as this study. It is expected that the findings from this study will suggest areas for additional research and will be of interest to researchers and professional educators, especially those involved in the development and use of BEL systems. Design/methodology/approach: This case study compares two groups of undergraduate students who completed a course designed to develop skills in using productivity software at a university in Thailand. After establishing the groups, one group learned in a BEL environment and the other in a TDL environment. In particular, the online training and assessment software application SIMnet was used in the BEL environment. Comparisons between results using BEL and TDL are made for different assessment results. Additional analyses of results for the BEL group examined gender differences and correlations between the number of attempts made on assessments and the levels of achievement. Findings: The findings indicated that for all of the assessments, the BEL group had a better performance than the TDL group. For the BEL group, additional analyses found no significant differences between the achievements of males and females and significant correlations between the numbers of attempts made on assessments and the results. Limitations of this case study are discussed, and the findings are expected to be of interest to researchers and professional educators, especially those involved in the development and use of BEL. Research limitations/implications: Learning content was restricted to the Excel spreadsheet in which different areas of content need to be studied. The software SIMnet was used by the BEL group, additional BEL software needs to be studied. The participants' characteristics – age, gender, culture and computer competency – were narrow scoped in which the study could include more varieties and also a larger sample size. Further studies should be designed to include more comparisons such a comparison between TDL group males and females. Originality/value: The findings from this limited case study suggest that a BEL learning environment is superior to a TDL environment. Also, a BEL environment is equally beneficial for male and female students. In particular, the BEL feature, which allows students to retake assessments, leads to improved learning performance equally for both males and females. In general, these findings support those reported in previous studies.